Prevalence and Pattern of Congenital Anomalies and Its Outcome at Chattagram Maa-O-Shishu General Hospital (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2017)
Background: Congenital anomalies are a major cause of perinatal and neonatal deaths, both in low and high-income countries.The aim of the study is to find out the overall incidence of clinically detectable Congenital anomalies in newborns in Chattagram Maa-O-Shishu General Hospital (CMOSH).Methods: A retrospective study was carried out from July 2010 to June 2011 to find out the incidence of congenital anomalies & its outcome at Chattagram Maa-O- Shishu General Hospital.Results: The total number of admission during this period was 2395 and total number of death was 141, out of which Congenital anomalies were 105. Among the Congenital anomalies, congenital heart disease was 62, Club foot was 9, Down syndrome was 8, Hydrocephalus was 5, Cleft lip & cleft palate was 5, Umbilical hernia was 4, Duodenal atresia was 3, Tongue tie was 3, Pierre robin syndrome was 3, Hisprung disease was 2 and Mermaid syndrome was 1.Conclusion: Heart defects were the most prevalent anomaly detected. Early prenatal diagnosis is therefore very helpful in decreasing perinatal mortality by allowing for the option of early termination of pregnancy.Chatt Maa Shi Hosp Med Coll J; Vol.16 (1); Jan 2017; Page 22-25